Pengaruh Kecerdasan Emosional Dan Kecerdasan Spiritual Terhadap Perilaku Sosial Anak Di Sekolah Dasar - Mahaju Salta, Noviarti (Yayasan Darusssalam Bengkulu, 2021)
Emotional behavior can be caused by various problems experienced by children, such as anger, frustration or other negative feelings. Therefore, there is a need for emotional intelligence which leads to decision making for individuals and must be accompanied by spiritual intelligence to develop individuals to think more broadly so that they have high insight in order to make individuals have good behavior in the surrounding environment. This research aims to determine the influence of emotional and spiritual intelligence on children's behavior at school. And the formulation of the problem in this research,